(untitled) (Sosquua, 2020)
Agradecemos la participación de los siguientes árbitros: Laura María Rodríguez Gutiérrez, Universidad de Antioquia, Colombia Luis Alfonso Vidal Ramírez, Colegio Mayor de Antioquia, Colombia Karen Paola Ochoa Espitia, Independientes, Colombia Olga Judith García Molano, Universidad Pedagógica de Colombia, Colombia Frank Ángel Lemoine Quintero, Universidad Laica Eloy Alfaro de Manabí, Ecuador Carolina Garzón Medina, Universidad Santo Tomás, Colombia Fabián Herrera Morales, Universidad de Caldas, Colombia Ricardo Varela Villalba, Universidad Autónoma de Bucaramanga, Colombia Arney Alfonso Vega Martínez, Universidad del Sinú, Colombia Carlos Andrés Carreño Hernández, Universidad Pedagógica de Colombia, Colombia Joaquín Humberto Fontecha Fontecha, Universidad de Santander, Colombia